Assessment of Technology Use and Technology Preferences for HIV Prevention Among Hispanic Women. (December 2018) - Villegas, Natalia; Cianelli, Rosina; de Tantillo, Lila; Warheit, Melanie; Montano, Nilda Peragallo; Ferrer, Lilian; Patel, Shefali
Introduction: HIV transmission presents an ongoing risk to Hispanic women, and prevention efforts remain a priority. The use of technology to prevent HIV transmission among Hispanic women and those of lower socioeconomic status underscore the need for effective implementation of technology. The purpose of this study is to describe technology preferences and predictors of the use of the internet for HIV prevention among low-income Hispanic women. Method: A secondary analysis was conducted using baseline data from an intervention to prevent HIV among 320 Hispanic women. The parent study was SEPA, Salud (health), Educación (education), Promoción (promotion), y [and] Autocuidado (self-care). Results: Most participants reported using personal technology, such as smartphones (90.6%), the internet (78.1%), and personal email (67.5%), every day. Most (71.3%) participants were open to learning about HIV education via the internet. In the logistic regression analysis, education and time since the last visit to the health care provider were significant predictors of the use of the internet to learn about HIV prevention, after controlling for age, living with the partner, and years living in the United States. Conclusion: Hispanic women demonstrated high levels of comfort with different forms of technology. These results indicated the potential to expand future HIV intervention efforts by implementing electronic dissemination of bilingual and culturally appropriate information for Hispanic women of diverse ages.